Growth characteristics and freezing tolerance of Zoysiagrass cultivars and experimental progeny - Okeyo, David Odiwuor (Kansas State University, 2010)
‘Meyer’ zoysiagrass (Zoysia japonica Steud.) has been the predominant cultivar in the transition zone of the U.S. since its release in 1952, primarily because of its good freezing tolerance. However, it is slow to establish and recover after sod harvest, and has poor shade tolerance. I evaluated ‘Meyer’, some commonly used cultivars, and 18 progeny from crosses of ‘Emerald’ (Z. japonica × Z. tenuifolia Willd. ex Thiele) × Z. japonica or Z. matrella (L.) Merr. × Z. japonica for stolon growth characteristics; sod tensile strength and recovery after harvest; shade resistance; freezing tolerance and its relationship to autumn color retention; and the potential influence of dehydrin and chitinase gene expression in freezing tolerance. After planting vegetative plugs, rates of stolon initiation (r = 0.66 in 2007, r = 0.94 in 2008) and elongation (r = 0.66 in 2007, r = 0.53 in 2008) were positively correlated (P < 0.05) with zoysiagrass coverage. At 60 days after sod harvest, recovery growth coverage ranged from 17% to 97% and a progeny from Z. matrella × Meyer (97% coverage) demonstrated superior sod recovery growth to Meyer (38% coverage). Under 68% silver maple (Acer saccharinum L.) tree shade, stolon number was reduced 38 to 95% and stolon length 9 to 70% compared to turf in full sun. Several progeny from crosses between Emerald or a Z. matrella x Z. japonica produced more and/or longer stolons than Meyer in the shade, suggesting potential for increased shade tolerance. Autumn color in October and November, 2007 was positively correlated (r = 0.44 and r = 0.58, P < 0.01) with the lethal temperature killing 50% of tillers (LT50) in December, 2007. All grasses except Cavalier and one progeny were equivalent to Meyer in freezing tolerance with LT50s ranging from -0.2 to -12.2 oC. Dehydrin-like (11.9, 23, 44.3, and 66.3 kDa) and chitinase (26.9 kDa) gene expression increased with cold acclimation and was similar among all grasses. In general, some new zoysiagrass progeny exhibited superior growth and/or stress tolerances compared to Meyer, which bodes well for potential release of a new cultivar for use in the transition zone.
Keywords: Zoysiagrass; Growth characteristics; Establishment rates; Sod production; Shade tolerance; Freezing tolerance; Agriculture, Plant Culture (0479)